2012
DOI: 10.5194/bg-9-527-2012
|View full text |Cite
|
Sign up to set email alerts
|

Biomass burning emissions estimated with a global fire assimilation system based on observed fire radiative power

Abstract: Abstract. The Global Fire Assimilation System (GFASv1.0) calculates biomass burning emissions by assimilating Fire Radiative Power (FRP) observations from the MODIS instruments onboard the Terra and Aqua satellites. It corrects for gaps in the observations, which are mostly due to cloud cover, and filters spurious FRP observations of volcanoes, gas flares and other industrial activity. The combustion rate is subsequently calculated with land cover-specific conversion factors. Emission factors for 40 gas-phase … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
1,454
1
14

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,208 publications
(1,500 citation statements)
references
References 45 publications
31
1,454
1
14
Order By: Relevance
“…Some recent inventories have started to use satellite retrievals of fire radiative power instead of burnt area which appears superior at least in some world regions (Kaiser et al, 2012). However, a comparison of five global biomass burning emission inventories based on different satellite fire or burned area products showed a large range of 365-1422 Tg CO emissions for the year 2003 (Stroppiana et al, 2010;Reddington et al, 2016).…”
Section: Biomass Burning Emissionsmentioning
confidence: 99%
“…Some recent inventories have started to use satellite retrievals of fire radiative power instead of burnt area which appears superior at least in some world regions (Kaiser et al, 2012). However, a comparison of five global biomass burning emission inventories based on different satellite fire or burned area products showed a large range of 365-1422 Tg CO emissions for the year 2003 (Stroppiana et al, 2010;Reddington et al, 2016).…”
Section: Biomass Burning Emissionsmentioning
confidence: 99%
“…With consistent aerosol emission and fire intensity information, GFASv1.1 provides an appropriate input data set for our simulations. Kaiser et al (2012) found that GFAS emissions implemented in the global circulation model ECMWF are only able to reproduce AOT observations in a reasonable way, if global GFAS wildfire emissions are multiplied by a global factor of 3.4. This zero-order approximation also provided reasonable global modeling results in studies by Huijnen et al (2012) andvon Hardenberg et al (2012) well as ECHAM5-HAM1.…”
Section: Emission Data Setsmentioning
confidence: 99%
“…The emission factors are from Akagi et al (2011), the estimated fuel loading are assigned using model results from Hoelzemann et al (2004), and the fraction of biomass burned is assigned as a function of tree cover (Wiedinmyer et al, 2006). The Global Fire Assimilation System (GFAS, Kaiser et al, 2012) calculates biomass burning emissions by assimilating Fire Radiative Power (FRP) observations from MODIS at a daily frequency and 0.5 • resolution and is available for the time period 2000-2013. After correcting the FRP observations for diurnal cycle, gaps etc., it is linked to dry matter combustion rate using Wooster et al (2005) and CH 4 emission factors from Andreae and Merlet (2001).…”
Section: Biomass Burningmentioning
confidence: 99%